Do Participatory Learning and Action Women's Groups Alone or Combined with Cash or Food Transfers Expand Women's Agency in Rural Nepal?. Issue 8 (3rd August 2019) - Gram, Lu; Morrison, Joanna; Saville, Naomi; Yadav, Shyam Sundar; Shrestha, Bhim; Manandhar, Dharma; Costello, Anthony; Skordis-Worrall, Jolene
Abstract: Participatory learning and action women's groups (PLA) have proven effective in reducing neonatal mortality in rural, high-mortality settings, but their impacts on women's agency in the household remain unknown. Cash transfer programmes have also long targeted female beneficiaries in the belief that this empowers women. Drawing on data from 1309 pregnant women in a four-arm cluster-randomised controlled trial in Nepal, we found little evidence for an impact of PLA alone or combined with unconditional food or cash transfers on women's agency in the household. Caution is advised before assuming PLA women's groups alone or with resource transfers necessarily empower women.